Modelo Logístico para el Transporte Intermunicipal de Pasajeros en la Provincia de Valderrama, Departamento de Boyacá. Carlos Arturo Cepeda Silva, Fabián Leonardo Cristancho Báez. 29 de mayo del 2023. Universidad Antonio - Cepeda Silva, Carlos Arturo; Cristancho Báez, Fabián Leonardo (Universidad Antonio Nariño, 2023)
This study proposes a logistic model for intermunicipal passenger transportation in the routes of influence of the province of Valderrama in the department of Boyaca; based on the determination of strategic stops with the objective of improving transportation efficiency and delimiting specific times in the routes. The first phase describes the transport operations carried out by the most influential servers in the province, identifying embarkation, disembarkation and transport activities. In the second part, an evaluation of the elements that may affect the transportation service in the studied area is carried out. Finally, the logistics model is developed, establishing a specific number of intermediate stops, determining fixed times to be maintained by each vehicle on the respective route